Combination of hanger reflex and optical flow enhances head rotation and influences its direction - Kon, Yuki; Kajimoto, Hiroyuki (Frontiers in Virtual Reality, 2026)
The Hanger Reflex (HR) is a tactile illusion phenomenon in which involuntary head rotation occurs when a person wears a wire hanger on the head. This rotation is induced by skin deformation caused by pressure on the head, and can occur in multiple directions, including yaw, pitch, and roll. However, it has been reported that the Hanger Reflex tends to occur more easily along certain axes, while being less likely along others. To address this limitation, we propose a method to alter the direction of head rotation induced by the Hanger Reflex by simultaneously presenting optical flow (OF) stimuli. In our experiment, we presented optical flow stimuli with varying directions and phases while inducing the Hanger Reflex. As a result, we confirmed that the head rotation, which originally occurred primarily along the yaw axis due to the Hanger Reflex, could be shifted to the pitch or roll axis depending on the direction of the presented optical flow. Furthermore, compared to the condition using only the Hanger Reflex, the combined condition with optical flow and the Hanger Reflex produced 2.1 to 2.7 times more head rotation in the pitch and roll directions. These findings suggest that a Hanger Reflex-based device, originally limited to yaw-axis head rotation, can be repurposed as a head rotation actuator in arbitrary directions when combined with optical flow. This has potential applications in the design of VR content.